Impact of Pulmonary Hypertension on Outcomes Following Aortic Valve Replacement for Aortic Valve Stenosis - Melby, Spencer J. (2011)
OBJECTIVE: The presence of pulmonary hypertension (PH) historically has been considered a significant risk factor affecting early and late outcomes following valve replacement. Given the number of recent advances in the management of PH following cardiac surgery a better understanding of the impact of PH on outcomes may assist in the clinical management of these patients. The purpose of this study was to determine if pulmonary hypertension remains a risk factor in the modern era for adverse outcomes following aortic valve replacement (AVR) for aortic valve stenosis. METHODS: From January 1996 to June 2009, 1,080 patients underwent AVR for primary aortic valve stenosis, of which 574 (53%) had normal systolic pulmonary artery pressures (sPAP) and 506 (47%) had PH. PH was defined as mild (sPAP 35-44 mmHg), moderate (45-59mmHg), or severe (≥ 60mmHg). In the group of patients with PH, 204 had postoperative echocardiograms. RESULTS: Operative mortality was significantly higher in patients with PH (47/506, 9% versus 31/574, 5%; p=0.02). The incidence of postoperative stroke was similar (p=0.14), but patients with PH had an increased median hospital LOS (8 versus 7 days, p=0.001) and an increased incidence of prolonged ventilation (26% versus 17%, p<0.001). Preoperative PH was an independent risk factor for decreased long term survival (RR 1.7, p=0.02). Those with persistent PH postoperatively had decreased survival. Five-year survival (Kaplan-Meier) was 78 ± 6% with normal sPAP and 77 ± 7% with mild PH postoperatively, compared to 64 ± 8% with moderate PH and 45 ± 12% with severe PH (p<0.001). CONCLUSION: In patients undergoing AVR, preoperative PH increased operative mortality and decreased long-term survival. Patients with persistent moderate or severe PH after AVR had decreased long-term survival. These data suggest that PH had a significant impact on outcomes in patients undergoing AVR and should be considered in preoperative risk assessment.